PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN CV PUTRA ABADI JAYA KECAMATAN TIGARAKSA - Nadia Satya Handayani; Sutrisno (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the effect of compensation and motivation on employee performance. This research uses a quantitative approach with a sample of 62 employees, a sampling technique using saturated sampling. Data collection techniques through primary and secondary data. Data analysis techniques use descriptive statistics, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination, t test and f test. The research results show that partial disturbances have a significant effect on employee performance. This can be proven from the simple linear regression equation Y = 23.954 + 0.376X and the value of tcount > ttable or (4.092 > 1.67065). Partially, motivation has a significant effect on employee performance, this can be proven by the equation Y = 17.253 + 0.548X and the value (5.902 > 1.67065). Simultaneously, motivation influences employee performance, this can be proven by the multiple linear regression equation Y = 18.285 + 0.065X₁ + 0.585X₂, the correlation value is 0.634, the coefficient of determination is 40.2%, the hypothesis test is obtained Fhitung > Ftabel or (19.809 > 3.15).